Riluzole rescues glutamate alterations, cognitive deficits, and tau pathology associated with P301L tau expression. (13th August 2015) - Hunsberger, Holly C.; Weitzner, Daniel S.; Rudy, Carolyn C.; Hickman, James E.; Libell, Eric M.; Speer, Rebecca R.; Gerhardt, Greg A.; Reed, Miranda N.
Abstract Hyperexcitability of the hippocampus is a commonly observed phenomenon in the years preceding a diagnosis of Alzheimer's disease (AD). Our previous work suggests a dysregulation in glutamate neurotransmission may mediate this hyperexcitability, and glutamate dysregulation correlates with cognitive deficits in the rTg(TauP301L)4510 mouse model of AD. To determine whether improving glutamate regulation would attenuate cognitive deficits and AD‐related pathology, TauP301L mice were treated with riluzole ( 12.5 mg/kg/day p.o.), an FDA‐approved drug for amyotrophic lateral sclerosis that lowers extracellular glutamate levels. Riluzole‐treated TauP301L mice exhibited improved performance in the water radial arm maze and the Morris water maze, associated with a decrease in glutamate release and an increase in glutamate uptake in the dentate gyrus, cornu ammonis 3 (CA3), and cornu ammonis 1 (CA1) regions of the hippocampus. Riluzole also attenuated the TauP301L‐mediated increase in hippocampal vesicular glutamate transporter 1, which packages glutamate into vesicles and influences glutamate release; and the TauP301L‐mediated decrease in hippocampal glutamate transporter 1, the major transporter responsible for removing glutamate from the extracellular space. The TauP301L‐mediated reduction in PSD‐95 expression, a marker of excitatory synapses in the hippocampus, was also rescued by riluzole. Riluzole treatment reduced total levels of tau, as well as the pathological phosphorylation and conformational changes in tau associated with the P301L mutation. These findings open new opportunities for the development of clinically applicable therapeutic approaches to regulate glutamate in vulnerable circuits for those at risk for the development of AD. <boxed-text content-type="graphic" id="jnc13230-blkfxd-0101" position="anchor" orientation="portrait"> </boxed-text> TauP301L mice exhibit increased glutamate release and decreased glutamate clearance, leading to increased extracellular glutamate and excitotoxicity. Riluzole treatment reduced glutamate release and increased glutamate clearance. Improved glutamate regulation was associated with improvements in learning and memory, an increase in PSD95 expression, and a decrease in tau pathology in riluzole‐treated TauP301L mice.